Spectators at a Wake Forest College vs Maryland football game, 1958. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 9-21-58 p.B4.
Spectators at a Wake Forest College vs Maryland football game, 1958. The game was played at Bowman Gray Stadium.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth